The Future of Indonesian Patronage Democracy: Political Campaign Financing Reform - Fitria Barokah; Hertanto Hertanto; Arizka Warganegara (PERSPEKTIF, 2022)
This study aims to see the relationship between patterns of patronage, clientelism, money politics, and campaign financing within the framework of patronage democracy that occurs in Indonesia. This paper uses the literature review method, the use of this method is related to the practice of patronage democracy and campaign financing which limits researchers in data collection. Data collection is done by collecting various books, scientific articles or journals related to the problem and research objectives. The results of this paper describe the pattern of patronage causing the large campaign costs incurred by each party and the candidate it nominates. The amount of money spent on campaigns can lead to acts of corruption. The solution offered in this paper has two points. First, campaign funding is financed 100% by the state, meaning that no other source of funds is allowed to enter the party. Thus, parties and candidates do not need to look for other sources of funds, so as to avoid the political potential of the party's debt of gratitude to fund owners from outside the party. Second, utilizing social media by conducting campaigns through social media because social media provides an open space with available features. Campaigns using social media can also minimize the expenditure of funds disbursed by the candidates. Thus, efforts to carry out money politics or vote buying will be reduced.